Implementation of monitoring system in Long Range and Blynk-based oyster mushroom production houses - S. Suroso; N. Nasron; Rizky Rian Nawawi (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
The goal of this research is to monitor the humidity and temperature conditions in the production facilities of oyster mushrooms using the Long Range data transmission and the Node MCU Esp32 microcontroller. The research utilizes a Long Range transmitter and receiver, which are placed at varying distances respectively, to determine the delay that the receiver receives. Based on the delay tests conducted at various distances, such as 200m, 400m, 600m, 800m, and 1km, this technology can provide a range of up to 600m.